2005
DOI: 10.1118/1.1997932
|View full text |Cite
|
Sign up to set email alerts
|

SU‐FF‐T‐204: In Vivo Force‐Torque Measurement During Prostate Brachytherapy

Abstract: Purpose: The main goal of this study is to measure the needle insertion force/torque (F/T), velocity/ acceleration (V/A), and tissue/organ deformation during actual brachytherapy procedures in the operating room (OR). These in vivo data will guide the design of a Robot‐Assisted Platform for Intratumoral Delivery (RAPID) system. Method and Materials: We have acquired F/T and V/A data from actual patients and a single surgeon placing brachytherapy needles in the OR using a hand‐held adapter equipped with a 6 deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The tissue with the 8 mm thickness was used for testing of the needles with micro-channels, while that with the 6 mm thickness for the needles with micro-dimples. This phantom tissue was commonly used as tissue-mimicking material during needle insertion tests due to its homogeneity [3,12]. In order to keep a constant pressure, the tissue was attached to the stage platform using double-sided tape.…”
Section: Friction Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The tissue with the 8 mm thickness was used for testing of the needles with micro-channels, while that with the 6 mm thickness for the needles with micro-dimples. This phantom tissue was commonly used as tissue-mimicking material during needle insertion tests due to its homogeneity [3,12]. In order to keep a constant pressure, the tissue was attached to the stage platform using double-sided tape.…”
Section: Friction Testmentioning
confidence: 99%
“…Inaccurate needle placement increases the possibility of vital tissue damage, misdiagnosis, under-/overdosing with radiation, etc. [3]. Alterovitz et al [4] demonstrated that inserting and retracting a needle into soft tissues exerted forces causing the surrounding soft tissue to displace and deform and resulting in substantial placement error.…”
Section: Introductionmentioning
confidence: 97%
“…The cutting force at the tip includes the plastic deformation from the act of cutting and the force resulting from tissue stiffness. Several studies have been conducted on modifying needle tip geometry to reduce the cutting forces [12][13][14][15]. A bevel tip needle has a smaller cutting force than a conical tip needle [15] but unlike a conical tip needle, it cannot travel in a straight path without rotating the needle about its axis.…”
Section: Introductionmentioning
confidence: 99%
“…This was less than the displacement observed when the capsule had the same stiffness as the prostate (2.61 cm). However, in-vivo experiments conducted at our institution indicate that once the needle penetrated the capsule comparatively less force is experienced [10], [11]. The initial results emphasize the importance of capsule in the dynamics of needle insertion prior to needle penetration into the prostate parenchyma, suggesting that a more in depth analysis of the capsule material properties should be undertaken.…”
Section: Discussionmentioning
confidence: 97%
“…In-vivo needle insertion force measurements conducted at our institution established that 10N is a typical maximal needle insertion during prostate brachytherapy [10], [11]. In the model where the capsule was given the same stiffness as the prostate parenchyma, the node at the site of loading experienced an overall displacement of 2.61 cm.…”
Section: B Mesh Deformationmentioning
confidence: 99%